Measurements and Distribution of Atmospheric Particulate-Bound Mercury: A Review - Zhang, Hui; Fu, Xuewu; Wang, Xun; Feng, Xinbin (Bulletin of Environmental Contamination and Toxicology, 2019)
Atmospheric particulate-bound mercury (PBM) plays an important role in the geochemical cycling of mercury (Hg). This study reviewed research progress of the PBM, including the possible emission and deposition pathways, measurement methods and the global distribution. The primary PBM sources are anthropogenic sources, but natural sources could be also a considerable contributor, for instance, chemical transport and dust in the arid and desert area. Different filter methods, such as quartz fibre filters, have been applied to the PBM measurement, and PBM can also be real-time monitored automatically. Generally, the average PBM concentrations were higher in the Northern Hemisphere than in the Southern Hemisphere. However, the PBM level of Antarctica is quite high. PBM concentrations were higher in the urban areas than in the remote areas, and there was a high PBM level in the developing countries. Moreover, high PBM concentrations were observed in the range 20 degrees-60 degrees of northern latitude.